PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK UNTUK PEMBELAJARAN IPS KELAS IV SEKOLAH DASAR - Edo Ari; M. Jaya Adi Putra; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is a research and development (Research & Development) or R&D that follows the ADDIE development model which includes five stages, namely: Analysis, Design, Development, Implementation and Evaluation which produces a Pop Up Book product for social studies learning for grade IV Elementary School. The subjects of the research trial were Class IV students at SD Negeri 004 Genting. The data collection instrument used was a questionnaire given to the validator to determine the feasibility of the pop up book learning media and a questionnaire given to teachers and students to determine the attractiveness of the product. Validation was carried out by two validators, namely, material experts and media experts. The validation results from the two validators show that the pop up book learning media for social studies learning has an overall average percentage of 80% that meets the "valid" criteria. Practicality was assessed by teachers and students and obtained the percentage of results of 95% and 92.2%, respectively, with those meeting the criteria of "very practical". So, the pop up book learning media for social studies learning can be used by students in elementary schools.Key Words: Instructional Media, Pop Up Book, IPS Learning